Xanthan gum-based nanocomposites for tissue engineering - Abu, Tariq; Showkat, Ahmad Bhawani; Khalid M, Alotaibi (Woodhead Publishing, 2021)
Xanthan gum (XG) is a naturally occurring exo-polysaccharide produced by the class of bacteria Xanthomonas campestris. This hetero polysaccharide produced from Gram-negative bacteria has various unique properties such as biocompatibility, biodegradability, cytocompatibility, highly viscous and pseudo-plastic nature, nontoxicity, and solubility in both cold and hot water, which make it a promising agent in biomedical and tissue engineering applications. Traditionally, XG is an important component for various industrial and biomedical applications as a thickener, emulsion stabilizer, and additive, and is widely used in food and food packaging, cosmetics, toiletries, drug delivery, etc. Recently, it has been used in tissue engineering applications after undergoing various chemical and physical modifications through incorporation of NPs. In this chapter, we discuss the applicability of XG nanocomposites obtained through various modifications in the field of biomedicine and tissue engineering.